Empowerment Strategies for MSMEs through Halal Certification in Ciro Ciroe Village - Fenny Hasanuddin; Yenni Anggrainingsi (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study explores the implementation of community empowerment initiatives through halal certification assistance as an effort to enhance the competitiveness of MSME products in Ciro Ciroe Village. Method: The community service activity was conducted on November 24, 2025, involving 30 participants from local MSMEs. The approach combined educational lectures, interactive discussions, and hands-on guidance. The implementation stages consisted of preparation, delivery of material through socialization sessions, question-and-answer interactions, and technical support for administrative requirements in the halal certification process. Results: The findings indicate that the program effectively increased participants’ knowledge and awareness regarding the importance of halal certification. MSME actors demonstrated improvements in maintaining product quality by adopting halal assurance practices. Additionally, the assistance helped streamline the certification application process, encouraged collaboration among participants, and addressed various practical challenges encountered during implementation. Overall, the study concludes that structured and continuous halal certification assistance plays a significant role in strengthening MSME capacity and improving product competitiveness, both in local and broader market contexts.